RESPONSE OF OAT CULTIVARS TO ETHEPHON AND BORON - & Abood, Addaheri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The aim of this study was to reduce the lodging and improve grain yield by evaluation the performance of some oat cultivars introduced into Iraq. A field experiment was conducted during two seasons of 2017-2018 and 2018-2019, included four cultivars (Genzania, Shafa, Carrolup and Hamel) under the influence of foliar spraying of ethephon at concentrations of 0, 500 and 1000 ppm, and foliar application of boron with concentrations of 0, 50 and 100 ppm. Using RCBD within split–split arrangement and three replicates. The results were revealed that Genzania was recorded the highest number of grains head-1 and grain yield 6.512 and 5.565 t ha-1 in the two seasons respectively. Shafa had the highest number of active tillers m-2 in both seasons and the highest single grain weight in the second season. Carrolup was produced the highest single grain weight in the first season. Spraying ethephon with concentrations of 500 and 1000 ppm increased stem diameter and number of active tillers m-2 for both seasons. Spraying 500 ppm of ethephon increased grain yield in the first season and reduced lodging rate in the second season. Ethephon with 1000 ppm reduced lodging rate in both seasons. Foliar application of boron with concentrations of 50 and 100 ppm increased plant height and grain yield in both seasons.